Practical guide for biomedical signals analysis using machine learning techniques : a MATLAB based approach - Subasi, Abdulhamit (Academic Press, an imprint of Elsevier, 2019)
This volume presents how machine learning and biomedical signal processing methods can be used in biomedical signal analysis. Different machine learning applications in biomedical signal analysis, including those for electrocardiogram, electroencephalogram and electromyogram are described in a practical and comprehensive way, helping readers with limited knowledge.